Plasmon-enhanced photocurrent generation from click-chemically modified graphene - Yenchalwar, Sandeep G.; Devarapalli, Rami Reddy; Deshmukh, Ashvini B.; Shelke, Manjusha V. (Chemistry-A European Journal, 2014)
The visible-light response of Au nanoparticles (AuNPs) assembled on rGO through different molecular bridges was investigated by transient photocurrent generation. We prepared rGO with two self-assembled monolayers (SAMs), one linear and the other with aromatic triazoles through a click cycloaddition reaction. A fivefold photocurrent enhancement was observed for triazole linkers over the aminopropyltrimethoxysilane (APTMS) linker. Cyclic voltammetry (CV) and impedance measurements also suggest fast electron transfer on account of the low resistance offered by the click-modified rGO surface whereby introduction of triazoles offers the efficient bridge between the donor AuNPs and acceptor rGO.
Keywords: Gold; graphene; Nanoparticles; photophysics; surface plasmon resonance